PENGARUH AUDIT TENURE, REPUTASI KAP, AUDIT DELAY, DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP OPINI AUDIT GOING CONCERN - Moratulus Gregorius Damor Myando; Herry Laksito (Diponegoro Journal of Accounting, 2023)
The purpose of this research is to examine the impact of audit tenure, reputation of accountant firm, audit delay, and previous year's audit opinion influence simultaneously toward going concern audit opinion in mining company that listed on the Indonesia Stock Exchange from 2020 to 2021.             This research used mining companies during the 2020-2021 with a total 114 samples. Sampling based on a purposive sampling method that follows certain criteria(s). Statistical testing was carried out using Logistic Regression with the help of SPSS version 25 computer program.             The results of this study show that audit delay and previous year's audit opinion have positive significant effect toward going concern audit opinion, Whereas, audit tenure and reputation of accountant firm do not influence going concern audit opinion.